EFIKASI DIRI MAHASISWA DALAM MEMBACA SELAMA LEARNING FROM HOME DI MASA PANDEMI COVID-19 - Yuyun - Widyawati; Umi Hanifah (Didaktika : Jurnal Kependidikan, 2020)
This study aims to explore the students’ self-efficacy on reading academic material during the Covid-19 pandemic. Self-efficacy as an element of social cognitive theory has a major role dealing with students’ motivation and learning process. Nowadays, during the massive spreads of Covid-19 virus in global, students must learn from their home in order to avoid the deployment of Covid-19 virus. During the activity of learning from home, students are asked to read a lot of academic materials. In relation to this,  self-efficacy is becoming an important variable. A qualitative descriptive method were used in this study. Data in this study taken from questionnaire consists of 27 items using Likert scale distributed online. The data collected analyzed using Ms. Excel. There were 30 participants in this study from East Java. The results of this study reveal that 40% of the students had a high self-efficacy level. Furthermore, more than a half of the students (60%) had a moderate level of self-efficacy. In contrast, there weren’t any student who have a low self-efficacy level. The study highlights that there is various level of students’ self-efficacy of reading academic material during the pandemic of Covid-19. Keywords: Learn from home, self-efficacy, reading, Covid-19